Goodpasture's disease following extracorporeal shock wave lithotripsy: a case report & literature review - Cranfield, Alistair (Clin Case Rep, 2015)
Shock wave lithotripsy may unmask epitopes within the glomerular basement membrane, leading to the formation of anti-glomerular basement membrane (GBM) antibodies and clinical disease in susceptible individuals. Although rare, our case highlights the need for vigilant monitoring of renal function following extracorporeal shock wave lithotripsy. This may allow for early recognition, treatment and improved outcome of anti-GBM disease.